2021
DOI: 10.1177/0021998320987640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanotubes modified with different concentrations of rare earth lanthanum on the mechanical and tribological properties of epoxy composites

Abstract: Rare earth modified acidified carbon nanotubes were prepared by functionalization of acidified carbon nanotubes with different concentrations of LaCl3. The modification results were characterized by Fourier-transform infrared and X-ray photoelectron spectroscopy. The rare earth successfully increases the surface activity of the acidified carbon nanotubes. Polymer matrix composites were prepared by using the rare earth modified acidified carbon nanotubes as the reinforcement in epoxy matrix. Mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Many studies have shown that the doping of rare earth elements can significantly improve the tribological properties of phenolic-based hybrid nanocomposites [ 19 , 22 , 24 , 25 ]. Yu et al designed a kind of polyimide nanocomposite filled with different rare earth oxides based on carbon nanotubes and graphene oxide, finding that filling with cerium oxide can dramatically reduce the friction coefficient and wear rate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the doping of rare earth elements can significantly improve the tribological properties of phenolic-based hybrid nanocomposites [ 19 , 22 , 24 , 25 ]. Yu et al designed a kind of polyimide nanocomposite filled with different rare earth oxides based on carbon nanotubes and graphene oxide, finding that filling with cerium oxide can dramatically reduce the friction coefficient and wear rate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%